HOTEL RESOR DI PANTAI MAJU SEBAGAI WATERFRONT ARCHITECTURE DENGAN PENDEKATAN METAPHORE - Danang Widiatmoko (Jurusan Arsitektur dan Perencanaan, 2021)
Pantai Maju is one of the islands on the north coast of Jakarta as a result of sea reclamation, so that the land in Pantai Maju is surrounded by marine waters, which architecturally represent an interesting natural potential. Designing a resort hotel on Pantai Maju will be interesting by applying waterfront architecture concept, especially on sites that are on the water side or sea side. A metaphorical approach needs to be done in architectural design, because with the location on the waterfront, it is very interesting if the figure of the resort hotel building has a strong form identity. The design method used is a series of design stages, starting from site potential analysis; analysis of design concepts; space program analysis; circulation analysis; analysis of the building mass. The conclusion of the design is a resort hotel in Pantai Maju which applies the concept of waterfront architecture and architecture metaphore. Keywords: hotel; metaphore; reclamation; resort; waterfrontAbstrakPantai Maju adalah salah satu pulau di pantai utara Jakarta sebagai hasil dari reklamasi laut, sehingga daratan di Pantai Maju dikelilingi oleh perairan laut, yang secara arsitektur merupakan potensi alam yang menarik. Perancangan Hotel Resor di pantai Maju sangat tepat apabila menerapkan konsep waterfront, terutama pada tapak yang berada di tepi perairan. Pendekatan metafora perlu dilakukan dalam perancangan arsitekturnya, sebab dengan lokasi tapak yang berada di tepi perairan, sangat menarik apabila sosok bangunan (figure) hotel resor tersebut mempunyai identitas bentuk yang kuat. Metode perancangan yang digunakan adalah; a) Segmen Kawasan Pantai Indah Kapuk; b) Diagram Isu Kawasan dan Konsep Penyelesaian Isu; c) Analisis Konsep Perancangan; d) Analisis Pemilihan Tapak dan Tapak Terpilih; e) Analisis Tapak; f) Konsep Massa Bangunan; g) Konsep Metafora; h) Zoning dan Program Ruang; i) Façade, Eksterior dan Interior. Kesimpulan dari perancangan adalah Hotel resort di Pantai Maju yang menerapkan konsep waterfront architecture, dan architecture metaphore.